CCN1 (Cyr61) Is Overexpressed in Human Osteoarthritic Cartilage and Inhibits ADAMTS‐4 (Aggrecanase 1) Activity. Issue 6 (June 2015) - Chijiiwa, Miyuki; Mochizuki, Satsuki; Kimura, Tokuhiro; Abe, Hitoshi; Tanaka, Yukie; Fujii, Yutaka; Shimizu, Hidenori; Enomoto, Hiroyuki; Toyama, Yoshiaki; Okada, Yasunori
<x xml:space="preserve">Abstract</x> Objective ADAMTS‐4, also called aggrecanase 1, is considered to play a key role in aggrecan degradation in human osteoarthritic (OA) cartilage, but information about regulators of ADAMTS‐4 aggrecanase activity remains limited. We undertook this study to search for molecules that modulate ADAMTS‐4 activity. Methods Molecules copurified with ADAMTS‐4 from ADAMTS‐4–transfected chondrocytic cells were sequenced by nanoscale liquid chromatography tandem mass spectrometry. Binding activity was determined by immunoprecipitation and solid‐phase binding assay. Effects on ADAMTS‐4 activity were examined by aggrecan digestion assay. Expression of the binding molecule in OA cartilage and chondrocytes was examined by immunohistochemistry and reverse transcription–polymerase chain reaction. Results We identified CCN1 (Cyr61) as an ADAMTS‐4–binding protein and showed specific binding to the ADAMTS‐4 cysteine‐rich domain. Aggrecanase activity of ADAMTS‐4 was inhibited by interaction with CCN1. Expression of messenger RNA for CCN1 was significantly higher in human OA cartilage than in normal cartilage. CCN1 was immunolocalized to chondrocytes in OA cartilage, showing direct correlations of immunoreactivity with the Mankin score of cartilage lesions and chondrocyte cloning. CCN1 and ADAMTS‐4 were commonly coexpressed in clustered chondrocytes. CCN1 expression in OA chondrocytes was down‐regulated by interleukin‐1α (IL‐1α) and up‐regulated by transforming growth factor β (TGFβ). ADAMTS‐4 expression was induced by treatment with IL‐1α or TGFβ, but aggrecanase activity was detected only under stimulation with IL‐1α. TGFβ‐treated chondrocytes exhibited aggrecanase activity when CCN1 expression was knocked down. Conclusion Our findings provide the first evidence that CCN1 suppresses ADAMTS‐4 activity and that CCN1 overexpression is directly correlated with chondrocyte cloning in OA cartilage. Our results suggest that the TGFβ/CCN1 axis plays a role in chondrocyte cluster formation through inhibition of ADAMTS‐4.